Cancer Patients’ Experiences of Forgiveness Therapy - Phillips, Lynda J.; Osborne, John W. (Canadian Journal of Counselling and Psychotherapy, 2011)
This study used a phenomenological method to investigate the lived-experiences patients who participated in a group therapy program called "forgiveness therapy." Theaim of the study was to develop an experientially-based understanding of the process of forgiveness. Five co-researchers participated (with the researcher) in six therapy sessions, as well as in unstructured intake and follow-up interviews. Therapy focused on the relief and dissipation of negative feelings and the resolution of painful psychological issues associated with cancer. A shared pattern emerged from analyses of participants' descriptions of their experiences. The existential themes of isolation/relationship, life/death, choice/responsibility, and meaning/ meaninglessness were issues for all participants. The process of forgiving involved a struggle with guilt, blame and revenge and a consequential growth in the understanding of the reciprocal nature of relationships. One individual's experience is discussed in detail in order to illustrate the process. The findings suggest that a forgiveness process can lead to catharsis and peace.